Methylammonium Chloride Additive in Lead Iodide Optimizing the Crystallization Process for Efficient Perovskite Solar Cells - Hongqiao Wang; Jingquan Zhang (International Journal of Photoenergy)
Perovskite solar cells (PSCs) were fabricated using a two-step spin-coating method with MACl added to the inorganic layer. The properties of the perovskite films were characterized by SEM, XRD, PL, UV-vis spectra, etc. The morphology of the PbI2 film was significantly changed, and the formation of MACl-related intermediate phase was observed at the grain boundaries. The grain size and crystallinity of the perovskite film increased, and the morphology at grain boundaries was optimized, while the composition of perovskite remained unchanged. The introduction of MACl improved the open circuit voltage (VOC) and fill factor (FF) of PSCs, and the optimal device efficiency reached 21.59%. This paper presents a new approach using additives in inorganic layers to optimize the crystallization process for efficient PSCs.